Praktik Jual Beli Mystery Box Melalui Shopee dan Vending Machine: (Studi Komparasi Hukum Bisnis Syari’ah Dan Hukum Perdata) - Yoga, Yoga; Azizah, Ninik (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2024)
This article discusses the practice of buying and selling mystery boxes through the Shopee marketplace and vending machines which are reviewed in sharia business law and civil law. This study uses a type of normative juridical legal research which is related to the conformity between phenomena occurring in the field and applicable regulations. Primary legal material is extracted from theory as well as legislation related to research and contracts on buying and selling mystery boxes using electronic media (online) in the Shopee marketplace and offline with vending machines. The results of this research indicate that the practice of buying and selling online mystery boxes from a sharia business law perspective is valid if the payment method is cash and if it is by payletter then it is not valid. Apart from that, buying and selling with a vending machine is the same as bai' mu'atah, but the practice of buying and selling mystery boxes with a vending machine is not legal, because it contains gharar. From a civil law perspective, buying and selling online mystery box cash systems is legal. If you want paylater payments, you must be competent according to the law. Buying and selling offline mystery boxes with vending machines is null and void because conditions 3 and 4 are not met. Keywords: Mystery Box, Vending Machine, Sharia Business Law, Civil Law